Advanced Access scheduling in general practice and use of primary care: a Danish population- based matched cohort study. Issue 5 (December 2020) - Bang, Maria; Pedersen, Henrik Schou; Bech, Bodil Hammer; Vestergaard, Claus Høstrup; Falhof, Jannik; Kjeldsen, Hans Christian; Vedsted, Peter; Vestergaard, Mogens
No abstract available